Manufacturing method of high Nb-TiAl alloy turbocharger

High Nb-TiAl alloy powder was prepared through rotary electrode powdering and SEBM forming processes, and heat treatment and fluorination were carried out, which solved the deformation and fracture problems of existing turbocharger materials under high speed and high temperature environments, and achieved efficient and stable turbocharger performance.

CN119839312AActive Publication Date: 2025-04-18UNIV OF SCI & TECH BEIJING

Patent Information

Application Number
CN202510190550.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-04-18
Estimated Expiration
2045-02-20

AI Technical Summary

Technical Problem

The existing turbocharger materials have problems such as deformation, carbon deposits, dynamic balance instability and blade fracture in high speed and high temperature environments, which is difficult to meet the high requirements of modern engines for material performance.

Method used

High Nb-TiAl alloy powder is prepared by rotary electrode powder making and SEBM forming processes. Through the integrated control technology of oxygen content throughout the process and heat treatment, fluorination treatment and other processes, a high Nb-TiAl alloy turbocharger is formed.

Benefits of technology

It improves the high-temperature oxidation resistance and creep performance of the turbocharger, reduces weight, improves the engine acceleration performance, reduces energy consumption and smoke, and avoids blade fracture failure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119839312A_ABST
    Figure CN119839312A_ABST
Patent Text Reader

Abstract

The invention provides a manufacturing method of a high Nb-TiAl alloy turbocharger, and belongs to the technical field of turbocharger manufacturing. The manufacturing method comprises the following steps: preparing high Nb-TiAl alloy powder by adopting a rotating electrode powder preparation method through a whole-process oxygen content integrated control technology; scanning and melting the high Nb-TiAl alloy powder layer by layer by adopting an SEBM forming process to form the high Nb-TiAl alloy turbocharger; and the high Nb-TiAl alloy turbocharger is subjected to heat treatment and fluorination treatment. According to the manufacturing process of the high Nb-TiAl alloy turbocharger, the uniformity of an alloy structure and the grain size can be improved, the weight of the turbocharger can be reduced, the high-temperature creep performance of the turbocharger can be improved, the stability is improved, the acceleration performance of an engine is further improved, energy consumption and smoke intensity are reduced, and the service life of the turbocharger is prolonged. Blade breakage and failure at the extremely high rotating speed are avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of turbocharger preparation, and in particular relates to a method for manufacturing a high Nb-TiAl alloy turbocharger. Background Art

[0002] The turbocharger is installed on the intake and exhaust manifold of the engine. It is in a high temperature, high pressure and high speed working condition. Its working environment is very harsh and the working requirements are relatively harsh. Therefore, the material molding process and processing technology are very demanding. The material is required to have good high temperature mechanical properties and good fatigue resistance and creep resistance.

[0003] The turbocharger turbine is a very critical and important part of the turbocharger. With the development of turbocharger technology, the material of the turbine is also constantly updated. In the past, the material commonly used for diesel engine turbocharger turbines was 20Cr3MoWV (A), but this material is only suitable for low-speed (about 40000r / min) and large turbochargers. As the speed of the turbocharger is getting higher and the volume is getting smaller, the exhaust temperature of the diesel engine has reached more than 750℃, and this material can no longer meet the use requirements of the turbocharger. At present, the turbocharger turbine of general automobiles generally uses K418 nickel-based high-temperature alloy. The turbocharger formed by this alloy has certain limitations, such as high processing difficulty, high weight, poor engine acceleration, high energy consumption, slow speed increase, high smoke density, and deformation of high-speed turbine blades. In addition, the surface of metal materials such as nickel-based K418 alloy often forms carbon deposits, and the dynamic balance is unstable under high-speed operation. In addition, the tiny carbon blocks that fall off hit the turbine blades at high speed at extremely high operating speeds, causing the blades to break and fail. Summary of the invention

[0004] The present disclosure aims to solve at least one of the technical problems existing in the prior art and provide a method for manufacturing a high Nb-TiAl alloy turbocharger.

[0005] The present disclosure provides a method for manufacturing a high Nb-TiAl alloy turbocharger, the manufacturing method comprising:

[0006] The high Nb-TiAl alloy powder is prepared by the rotating electrode powder making method through the integrated control technology of oxygen content in the whole process;

[0007] The high Nb-TiAl alloy powder is scanned and melted layer by layer by using a SEBM forming process to form a high Nb-TiAl alloy turbocharger;

[0008] The high Nb-TiAl alloy turbocharger is subjected to heat treatment and fluorination treatment.

[0009] Optionally, a rotating electrode powder making method is used to prepare high Nb-TiAl alloy powder by an integrated control technology of oxygen content in the whole process, including:

[0010] The titanium, aluminum and niobium metal powders are subjected to two consumable smelting processes and one induction smelting process to form electrode rods, wherein the oxygen content of the electrode rods is below 500 ppm;

[0011] Under the condition that the oxygen content is less than 0.2ppm, the electrode rod is crushed by using a plasma rotating electrode powder making device, and the crushed powder is screened and packaged under an argon atmosphere to form a high Nb-TiAl alloy powder, wherein the oxygen content of the high Nb-TiAl alloy powder is less than 670ppm.

[0012] Optionally, in the high Nb-TiAl alloy powder, the atomic ratio of titanium, aluminum and niobium is (40-50):(40-50):(4-10).

[0013] Optionally, the high Nb-TiAl alloy powder is Ti-45Al-8Nb alloy powder.

[0014] Optionally, the SEBM forming process is used to scan and melt the high Nb-TiAl alloy powder layer by layer to form a high Nb-TiAl alloy turbocharger, comprising:

[0015] Preheating the substrate;

[0016] Spreading powder on the substrate according to a preset powder layer thickness, and preheating the powder layer with a preheating current to micro-sinter the high Nb-TiAl alloy powder;

[0017] Selectively melting the powder to form a molten layer;

[0018] Preheating the molten layer for a second time;

[0019] The powder is spread on the substrate repeatedly and the molten powder is scanned layer by layer to form a high Nb-TiAl alloy turbocharger.

[0020] Optionally, the substrate is preheated at a temperature of 1100-1200° C. for a time of 10-30 min; and / or,

[0021] The temperature of preheating the powder layer is 1100-1200°C; and / or,

[0022] The temperature for secondary preheating the molten layer is 1100-1200°C.

[0023] Optionally, the process parameters for selective melting of the powder are as follows: melting current is 10-12.5 mA, electron beam scanning speed is 3.5-5 m / s, scanning spacing is 100 μm, powder layer height is 40-60 μm, and density is greater than 98%.

[0024] Optionally, the high Nb-TiAl alloy turbocharger is subjected to heat treatment, comprising:

[0025] The high Nb-TiAl alloy turbocharger is first heat treated at 1400-1500° C. for 20-40 min;

[0026] A second heat treatment of the high Nb-TiAl alloy turbocharger at 1300-1400° C. for 50-60 min;

[0027] The high Nb-TiAl alloy turbocharger is subjected to a third heat treatment at 900-1000° C. for 50-60 min.

[0028] Optionally, the high Nb-TiAl alloy turbocharger is first heat treated at 1450° C. for 30 min;

[0029] A second heat treatment of the high Nb-TiAl alloy turbocharger at 1350° C. for 60 min;

[0030] The high Nb-TiAl alloy turbocharger was subjected to a third heat treatment at 950° C. for 60 min.

[0031] Optionally, the high Nb-TiAl alloy turbocharger is subjected to fluorination treatment, comprising:

[0032] In a fluorine-containing electrolyte, a high Nb-TiAl alloy turbocharger is treated for 10-30 minutes using liquid phase electrolytic plasma deposition technology to implant fluorine ions into the surface of the high Nb-TiAl alloy and grow a F-containing oxide film in situ.

[0033] Optionally, the fluorine-containing electrolyte comprises a first component and a second component; wherein,

[0034] The first component is sodium fluoride or potassium fluoride;

[0035] The second component is ethanol or ethylene glycol.

[0036] The present disclosure proposes a method for manufacturing a high Nb-TiAl alloy turbocharger, comprising: preparing high Nb-TiAl alloy powder by a rotating electrode powder making method through a full-process oxygen content integrated control technology; using a SEBM forming process to scan and melt the high Nb-TiAl alloy powder layer by layer to form a high Nb-TiAl alloy turbocharger; and heat treating and fluoriding the high Nb-TiAl alloy turbocharger. The alloy components and manufacturing processes used in the present disclosure can improve the uniformity of the alloy structure and the size of the structure, reduce the weight of the turbocharger, and can also improve the high-temperature creep performance of the turbocharger, improve stability, further improve the engine acceleration performance, reduce energy consumption and smoke density, and avoid blade fracture failure at extremely high speeds. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 It is a flowchart of a method for manufacturing a high Nb-TiAl alloy turbocharger according to a specific embodiment of the present disclosure;

[0038] Figure 2 XRD diffraction patterns of high Nb-TiAl alloy turbocharger samples obtained under different forming parameters in Example 1 of the present disclosure; (a) 10 mA; (b) 10.5 mA; (c) 11 mA; (d) 11.5 mA; (e) 12.5 mA;

[0039] Figure 3 The tensile fracture morphology of the high Nb-TiAl alloy turbocharger sample obtained in Example 1 of the present disclosure under the conditions of electron beam scanning speed of 3.5 m / s and melting current of 10 mA and 11 mA; (ab) 10 mA-3.5 m / s; (cd) 11 mA-3.5 m / s;

[0040] Figure 4 The tensile stress-strain curves of the high Nb-TiAl alloy turbocharger sample were obtained for Example 1 of the present disclosure under the conditions of electron beam scanning speed of 3.5 m / s and melting current of 10 mA and 11 mA; (a) 10 mA-3.5 m / s; (b) 11 mA-3.5 m / s;

[0041] Figure 5 The creep results of the high Nb-TiAl alloy turbocharger sample were obtained for Example 1 of the present disclosure under the conditions of electron beam scanning speed of 3.5 m / s and melting current of 10 mA and 11 mA; (a) 10 mA-3.5 m / s; (b) 11 mA-3.5 m / s;

[0042] Figure 6 The engine acceleration curves of the high Nb-TiAl alloy turbocharger and the K418 alloy turbocharger of Example 1 of the present disclosure;

[0043] Figure 7 The smoke curves of the high Nb-TiAl alloy turbocharger and the K418 alloy turbocharger of Example 1 of the present disclosure;

[0044] Figure 8 The fuel consumption conversion ratio of the high Nb-TiAl alloy turbocharger and the K418 alloy turbocharger in the above-water condition of Example 1 of the present disclosure;

[0045] Fig. 9 The tensile fracture morphology of the high Nb-TiAl alloy sample was obtained under the conditions of electron beam scanning speed of 3.5 m / s and melting current of 10 mA and 11 mA for comparative example 1 of the present disclosure; (ab) 10 mA-3.5 m / s; (cd) 11 mA-3.5 m / s;

[0046] Fig.10 The tensile stress-strain curves of the high Nb-TiAl alloy sample were obtained for Comparative Example 1 of the present disclosure under the conditions of electron beam scanning speed of 3.5 m / s and melting current of 10 mA and 11 mA; (a) 10 mA-3.5 m / s; (b) 11 mA-3.5 m / s;

[0047] Fig.11 The creep results of high Nb-TiAl alloy samples were obtained for comparative example 1 of the present disclosure at an electron beam scanning speed of 3.5 m / s and a melting current of 10 mA and 11 mA; (a)

[0048] 10mA-3.5m / s; (b) 11mA-3.5m / s. DETAILED DESCRIPTION

[0049] In order to enable those skilled in the art to better understand the technical solution of the present disclosure, the present disclosure is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. It should be understood that the specific embodiments described herein are only used to explain the present disclosure and are part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the embodiments of the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure.

[0050] like Figure 1 As shown, the present disclosure provides a method S100 for manufacturing a high Nb-TiAl alloy turbocharger, which specifically includes the following steps S110 to S130:

[0051] S110. A rotating electrode powder making method is used to prepare high Nb-TiAl alloy powder by using an integrated control technology for oxygen content in the entire process.

[0052] Specifically, titanium, aluminum, and niobium metal powders are subjected to two consumable smeltings and one induction smelting to form electrode rods, the oxygen content of which is below 500ppm; thereafter, the electrode rods are crushed using a plasma rotating electrode powder making device under the condition that the oxygen content is less than 0.2ppm, and the crushed powders are screened and packaged under an argon atmosphere to form high Nb-TiAl alloy powders, and the oxygen content of the obtained high Nb-TiAl alloy powders is less than 670ppm. This embodiment can reduce alloy defects, improve the strength and toughness of the alloy, and meet the requirements for stable operation of components under high temperature and high pressure environments by controlling the oxygen content of the alloy powders. At the same time, the low oxygen content helps to reduce the weak points inside the alloy, making it more difficult for the alloy to produce fatigue cracks under cyclic loads, thereby improving fatigue resistance, especially for aerospace parts working under alternating stresses, which can extend their service life and reduce maintenance costs.

[0053] In some preferred embodiments, the temperature range of the two consumable smeltings is 1400-1600°C, and the temperature range of the one induction smelting is 1500-1650°C.

[0054] In other preferred embodiments, in the high Nb-TiAl alloy powder, the atomic ratio of titanium, aluminum and niobium is (40-50):(40-50):(4-10). For example, the high Nb-TiAl alloy powder uses Ti-45Al-8Nb alloy powder. Of course, alloy powders with other atomic ratios can also be used, and there is no specific limitation on this.

[0055] Compared with the current use of K418 nickel-based high-temperature alloy as a turbocharger, this embodiment uses Ti, Al, and Nb as turbocharger raw materials, which has the advantages of low density, can reduce the weight of the rotating parts of the turbocharger, can reduce the moment of inertia when the car is running, and improve the response speed of the turbocharger, so that the engine can adjust the intake volume more quickly under different working conditions, improve power performance and fuel economy. Secondly, high Nb-TiAl alloy can provide higher strength and rigidity, and can ensure the structural stability of the parts in the working environment where the supercharger rotates at high speed and withstands high temperature and high pressure, can withstand greater pressure and stress, is not easy to deform and damage, and improves the reliability and service life of the supercharger.

[0056] S120, SEBM forming process is used to scan and melt high Nb-TiAl alloy powder layer by layer to form a high Nb-TiAl alloy turbocharger.

[0057] Specifically, step S120 includes the following steps:

[0058] 1) Preheating the substrate, wherein the substrate preheating temperature is preferably 1100-1200°C, for example, 1100°C, 1150°C, 1200°C, etc., and the time is preferably 10-30 minutes, and 10 minutes, 20 minutes, 30 minutes, etc. Preheating the substrate can make the TiAl alloy turbocharger have toughness and plasticity during the forming process; at the same time, reduce thermal stress and prevent the generation of thermal cracks; preheating the substrate can also ensure the initial powder layer is slightly melted, so that the initial powder layer is sintered firmly and does not produce "powder blowing" due to the impact of the electron beam.

[0059] 2) Spread the powder on the substrate according to a preset powder layer thickness, and preheat the powder layer with a preheating current to micro-sinter the high Nb-TiAl alloy powder, wherein the powder is spread on the substrate according to a thickness of 40-60 μm, and the preheating temperature is 1100-1200° C. By preheating the high Nb-TiAl alloy powder during the powder spreading process, the high Nb-TiAl alloy powder is micro-sintered to reduce fluidity and improve powder bed stability. The high Nb-TiAl alloy powder is slightly sintered to withstand the impact of the electron beam, and then selective melting is performed, which can further avoid powder blowing.

[0060] 3) Selectively melt the high Nb-TiAl alloy powder to form a molten layer.

[0061] Specifically, according to the preset three-dimensional model of the turbocharger, the powder in the target area of ​​the powder layer is melted to make it completely melted, and it is ensured that the layers are densely bonded without fusion defects. The process parameters for selective melting of high Nb-TiAl alloy powder are as follows: melting current is 10-12.5mA, electron beam scanning speed is 3.5-5m / s, scanning spacing is 100μm, powder layer height is 40-60μm, and density is 98.05-99.89%.

[0062] In some preferred embodiments, the melting current is preferably 10 mA, 10.5 mA, 11 mA, within which range, the powder blowing phenomenon is very slight. The electron beam scanning speed is preferably 3.5 m / s, 4 m / s, and a lower speed is conducive to forming a lamellar structure with good morphology.

[0063] 4) Preheating the molten layer for a second time.

[0064] Specifically, after the melting scan is completed, the molten layer is preheated for a second time with an electron beam, wherein the temperature of the second preheating of the molten layer is 1100-1200°C, which reduces the cooling rate of the molten layer and avoids the formation of a temperature gradient difference. The second preheating can also promote the stability of the powder layer when the powder is spread next time.

[0065] 5) Repeat the process of spreading powder on a substrate and melting the powder layer by layer to form a high Nb-TiAl alloy turbocharger.

[0066] Specifically, repeat steps 2) to 4), spread powder on the substrate layer by layer, and melt the preset area of ​​the powder layer. After forming the melt layer, continue to spread powder on the melt layer and melt it, and spread and melt powder layer by layer in sequence until the desired high Nb-TiAl alloy turbocharger is formed. It should be understood that after the selective melting, in order to accelerate the cooling rate of the formed part, argon gas can be filled into the chamber, and when it is cooled to room temperature, the formed sample is taken out of the chamber and the unmelted powder is removed.

[0067] This embodiment adopts the SEBM forming process to scan and melt the high Nb-TiAl alloy powder layer by layer to form a high Nb-TiAl alloy turbocharger, which can manufacture a turbine with a complex structure according to a three-dimensional model. The high-energy-density electron beam is used as a heat source to quickly melt and solidify the alloy powder, achieve good metallurgical bonding between the powder particles, and form a microstructure with high density and no obvious defects. At the same time, it can also refine the grain structure to form a fine and uniform grain structure, inhibit the formation of harmful phases, and thereby improve the overall mechanical properties and high-temperature performance of the turbocharger.

[0068] S130. Heat treatment and fluorination treatment of high Nb-TiAl alloy turbocharger.

[0069] Specifically, this embodiment adopts a heat treatment process to obtain a uniformly distributed microstructure, wherein the heat treatment process includes three parts, as follows:

[0070] The high Nb-TiAl alloy turbocharger is first heat treated at 1400-1500°C for 20-40 minutes, that is, the temperature is firstly heated to the β phase single phase region and kept for a short time, cooled to make it undergo β→α phase transformation, and then cooled to retain the α phase as much as possible.

[0071] The high Nb-TiAl alloy turbocharger is subjected to a second heat treatment at 1300-1400° C. for 50-60 min, and then heated to 1350° C. and furnace cooled in order to obtain a uniform lamellar structure.

[0072] The high Nb-TiAl alloy turbocharger is subjected to a third heat treatment at 900-1000° C. for 50-60 min.

[0073] The heat treatment process used in this embodiment can transform the residual α phase in the high Nb-TiAl alloy into an ordered α 2 Phase (α→α 2 ), the processed lamellar structure is composed of equiaxed and a small amount of columnar, and the lamellar size is also in the range of 40-60μm. The B2 phase can be eliminated by heat treatment, and the microstructure of SEBM-formed high Nb-TiAl alloy is optimized. The microstructure consists of γ lath, B2 phase and γ / α2 The flakes are transformed into small-sized full-γ / α 2 Lamellar structure, B2 phase content is reduced. It can hinder dislocation movement and crack propagation, further strengthen the performance of the alloy, and optimize the alloy at the microstructural level. The full γ / α2 lamellar structure has good high-temperature stability and can maintain good organizational structure and performance under high temperature environment. Compared with the organization containing B2 phase, the γ / α2 lamellar structure is not easy to undergo phase transformation and grain growth at high temperature, and can effectively resist high-temperature creep and oxidation, thereby improving the service life and reliability of high Nb-TiAl alloy turbochargers at high temperatures. Secondly, the γ / α2 lamellar structure can form a denser oxide film to prevent further intrusion of corrosive media, thereby improving the corrosion resistance of high Nb-TiAl alloy turbochargers and making them have better durability in harsh working environments. In other words, this embodiment further heat treats the high Nb-TiAl alloy turbocharger, which helps to improve the microstructure, improve the strength and hardness of the turbocharger, improve the mechanical properties, etc., and prevent the high Nb-TiAl alloy turbocharger from oxidizing in a high temperature environment (e.g., 700°C).

[0074] Furthermore, the high Nb-TiAl alloy turbocharger is subjected to fluorination treatment in this embodiment, comprising:

[0075] In a fluorine-containing electrolyte, a high Nb-TiAl alloy turbocharger is treated for 10-30 minutes using liquid phase electrolytic plasma deposition technology. Fluorine ions are injected into the surface of the high Nb-TiAl alloy turbocharger sample to grow a layer of F-containing oxide film in situ. The fluorination treatment can enhance the stability of the material structure, increase the Al content on the alloy surface, and easily diffuse aluminum fluoride from holes or cracks to the alloy surface at high temperature. The oxidation process is directed to Al 2 O 3 transformation, continuously forming dense Al 2 O 3 Improve the oxidation resistance, increase the stability of the material structure on the basis of improving the microstructure by heat treatment and reducing the B2 phase content, and further improve the creep performance. 2 O 3 The presence of can strengthen the grain boundaries of the alloy. In the creep process, the grain boundaries are prone to sliding and deformation, and this oxide film can hinder the sliding of the grain boundaries and improve the creep resistance of the grain boundaries, thereby improving the overall creep performance of the high Nb-TiAl alloy turbocharger, and more effectively resisting creep deformation under long-term high temperature and stress.

[0076] In some preferred embodiments, the fluorine-containing electrolyte includes a first component and a second component; wherein the first component is sodium fluoride or potassium fluoride; and the second component is ethanol or ethylene glycol. For example, the fluorine-containing electrolyte is sodium fluoride and ethanol, sodium fluoride and ethylene glycol, potassium fluoride and ethanol, or potassium fluoride and ethylene glycol.

[0077] In this embodiment, a fluoride film can be formed on the alloy surface by fluoriding the formed sample, thereby reducing the friction coefficient of the turbocharger during operation. For example, the contact surface between the turbine and the bearings, seals and other components can be reduced by fluoridation to improve the mechanical efficiency. Secondly, the fluoridation film can fill the microscopic defects and pores on the alloy surface, making the surface smoother, reducing the generation and shedding of wear particles, and at the same time improving the structural stability, improving its creep performance, and extending the service life of the high Nb-TiAl alloy turbocharger.

[0078] The manufacturing method of the high Nb-TiAl alloy turbocharger will be further described below in conjunction with specific embodiments:

[0079] Example 1

[0080] This example provides a high Nb-TiAl alloy turbocharger, comprising the following steps:

[0081] S1. Titanium, aluminum and niobium metal powders are subjected to two consumable smelting processes at 1500°C and one induction smelting process at 1550°C to form electrode rods, the oxygen content of which is below 500ppm. Thereafter, the electrode rods are crushed by plasma rotating electrode powder making equipment under the condition that the oxygen content is less than 0.2ppm, and the crushed powders are sieved and packaged under argon atmosphere to form Ti-45Al-8Nb alloy powder, the oxygen content of the obtained Ti-45Al-8Nb alloy powder being lower than 670ppm.

[0082] S2, preheat the substrate at 1100°C for 10 minutes, spread the Ti-45Al-8Nb alloy powder of step S1 on the substrate to a thickness of 50 μm, preheat the laid powder layer at 1100°C, and completely melt the powder in the target area to ensure that the layers are densely combined without fusion defects. The process parameters for selective melting of the powder are as follows: the melting current is 10mA, 10.5mA, 11mA, 11.5mA, and 12.5mA, respectively, the electron beam scanning speed is 3.5m / s, 4.0m / s, 4.5m / s, and 5.0m / s, respectively, the scanning spacing is 100μm, and the powder layer height is 50μm. The temperature for the secondary preheating of the molten layer is 1100°C, and the powder is spread layer by layer on the substrate and melted repeatedly to form a Ti-45Al-8Nb alloy turbocharger with a density of more than 98%.

[0083] like Figure 2 As shown, the diffraction peaks of the sample formed under the above process parameters in this embodiment are all composed of γ phase, α 2 The strongest diffraction peak in the samples with different beam currents corresponds to γ(111); at 40.285°, it corresponds to the diffraction peak of B2 phase (110), and the peak intensity of the sample obtained under the conditions of 10mA-11.5mA has no obvious change. When the beam current is 12.5mA, the diffraction peak intensity of the sample suddenly increases; for α 2 Phase, under the conditions of various beam currents and scanning speeds, the diffraction peak position and intensity of the sample have no obvious difference, and the formed turbocharger sample is Ti-45Al-8Nb alloy.

[0084] S3. The Ti-45Al-8Nb alloy turbocharger is subjected to a first heat treatment at 1450°C for 30 min, a second heat treatment at 1350°C for 60 min, and a third heat treatment at 950°C for 60 min.

[0085] S4. In a fluorine-containing electrolyte, a Ti-45Al-8Nb alloy turbocharger is treated for 10 minutes by liquid phase electrolytic plasma deposition technology to implant fluorine ions into the surface of the Ti-45Al-8Nb alloy and grow a layer of F-containing oxide film in situ. The electrolyte includes sodium fluoride and ethanol.

[0086] The tensile properties, port morphology and creep of the samples are analyzed under the conditions of electron beam scanning speed of 3.5 m / s and melting current of 10 mA and 11 mA.

[0087] Specifically, Figure 3 As shown in the figure, a large number of step-shaped tear bridges were found on the fracture of the heat-treated specimens. At the same time, the fracture mode of the full lamellar structure after heat treatment is generally manifested as through-lamellar fracture and along-lamellar fracture. This phenomenon is generally related to the orientation of the lamellar and the direction of the tensile force axis. The fracture mode under the 10mA-3.5m / s and 11mA-3.5m / s processes is a mixed fracture along the lamellar and through-lamellar fracture.

[0088] Specifically, Figure 4As shown in the figure, the tensile properties of the samples obtained under the above conditions at 700°C are analyzed. The tensile strength of the Ti-45Al-8Nb alloy turbocharger obtained by the 10mA-3.5m / s process and heat treatment reaches 500.95MPa, and the elongation of the sample reaches 8.12%; the tensile strength of the Ti-45Al-8Nb alloy turbocharger obtained by the 11mA-3.5m / s process and heat treatment reaches 482.2MPa, and the elongation reaches 7.02%. Heat treatment alleviates the degradation behavior of the organization, so that the equiaxed or columnar lamellar organization is shown in the forming direction, and there is no thick γ lath. Therefore, after heat treatment, the lamellar organization increases and other structures such as dual-state organization decrease, which makes the strength of the sample decrease and the plasticity increase compared with that before heat treatment. In this way, the turbocharger can better adapt to the stress concentration and deformation in operation, avoid sudden brittle fracture, and improve reliability.

[0089] Specifically, Figure 5 As shown, the turbocharger sample treated with fluorination maintains a shorter time in the first stage of creep. The sample obtained under the condition of 10mA-3.5m / s lasts for about 100h, and the sample obtained under the condition of 11mA-3.5m / s lasts for about 130h. There is no trend of entering the acceleration stage from the steady-state creep stage to 500h. At this time, the creep amount of 100h is reduced. At 100h, the creep amount of the sample obtained under the condition of 10mA-3.5m / s is 0.165%; at 100h, the creep amount of the sample obtained under the condition of 11mA-3.5m / s is 0.242%. This may be due to the pore defects that cause its initial creep amount to be higher than that of the double-treated 10mA-3.5m / s, but lower than the 500h creep amount of the sample of Comparative Example 1.

[0090] Furthermore, this embodiment compares and analyzes a Ti-45Al-8Nb alloy turbocharger formed under the condition of 10 mA-3.5 m / s with a conventional K418 turbocharger.

[0091] like Figure 6 As shown, compared with a diesel engine equipped with a K418 turbocharger, a certain type of diesel engine equipped with the Ti-45Al-8Nb alloy turbocharger of this embodiment has a 35% increase in full-load acceleration. The engine based on the Ti-45Al-8Nb alloy turbocharger has higher acceleration, faster speed response, and higher efficiency.

[0092] like Figure 7 As shown, compared with a diesel engine equipped with a K418 turbocharger, a certain type of diesel engine equipped with the Ti-45Al-8Nb alloy turbocharger of this embodiment has a full-steady-state smoke density reduced by 0.2 bo.

[0093] like Figure 8As shown, compared with a diesel engine equipped with a K418 turbocharger, a certain type of diesel engine equipped with the Ti-45Al-8Nb alloy turbocharger of this embodiment has a specific fuel consumption reduced by 3g / kW·h and an overall mechanical efficiency increased by 1.5%.

[0094] In summary, the turbocharger manufactured using the alloy and process of this embodiment can effectively reduce the difficulty of processing, reduce the weight of the turbocharger, improve engine acceleration, reduce energy consumption and smoke density, and improve stability.

[0095] Comparative Example 1

[0096] The turbocharger manufacturing method of this comparative example is the same as that of Example 1, except that steps S3 and S4 are removed, that is, the high Nb-TiAl alloy turbocharger is formed by adopting the SEBM forming process.

[0097] Similarly, in this comparative example, the tensile properties, port morphology, creep amount and other aspects of the samples obtained with an electron beam scanning speed of 3.5 m / s and a melting current of 10 mA and 11 mA were analyzed.

[0098] Specifically, Fig. 9 As shown in the figure, the fracture morphology of the alloy sample without heat treatment shows brittle fracture characteristics, containing a large number of small dissociation surfaces and tearing cracks. The fracture morphology of the sample under the condition of 10mA-3.5m / s has a small part of cleavage fracture through the layer, some microcracks and dimples. The whole fracture morphology looks like a smooth cross-section, and the fracture mode is brittle fracture; the fracture mode of the sample obtained under the condition of 11mA-3.5m / s is also brittle fracture. The difference from the fracture morphology of the sample obtained by the process of 10mA-3.5m / s is that there are more microcracks, which shows that the sample without heat treatment is prone to brittle fracture.

[0099] Specifically, Fig.10 As shown, the tensile strength of the sample obtained under the 10mA-3.5m / s condition reached 670.15MPa, and the elongation of the sample reached 4.15%. The tensile strength of the sample obtained under the 11mA-3.5m / s process reached 619.19MPa, and the elongation reached 3.51%.

[0100] Specifically, Fig.11 As shown in the figure, the creep amount of the sample obtained under the condition of 10mA-3.5m / s at 100h is 0.204%, and the creep amount of the sample obtained under the condition of 11mA-3.5m / s at 100h is 0.202%. After the two samples were subjected to the creep test of 500MPa and 500h, the samples maintained the first stage of creep for 180h, and then entered the steady state stage, and did not show the trend of entering the accelerated stage until 500h.

[0101] In summary, by comparing Comparative Example 1 with Example 1, it can be seen that after appropriate heat treatment, the SEBM-formed Ti-45Al-8Nb alloy turbocharger has a microstructure dominated by equiaxed and columnar lamellar structures, and the distribution range of the lamellar size is basically 40-60 μm; the lamellar structure-lath γ and α in the forming direction before heat treatment is replaced. 2 The organization of the grains is not the same, but the organization is consistent in the forming direction. At the same time, a bright band of light and dark is produced at the boundary of the lamellar organization. The dark part has a different organization with contrast from the alternating light part. That is, the uniformity of the organization, the size of the organization and the elongation can be improved by regulating the heat treatment process, thereby improving the fatigue resistance and seismic resistance. Secondly, a dense Al 2 O 3 The surface of the alloy that has not been electrochemically fluorinated first forms a loose TiO 2 The thin film, O atoms will diffuse into the alloy through the film, making the oxidation behavior more serious, which is not conducive to the stability of the structure. In other words, the fluorination treatment further improves the structural stability of the TiAl alloy, which not only ensures the reduction of the initial creep amount to meet the service requirements, but also promotes the reduction of the creep amount under the long-term action of temperature and stress.

[0102] The present disclosure provides a method for manufacturing a high Nb-TiAl alloy turbocharger, which has the following beneficial effects compared with the prior art:

[0103] First, the present invention adjusts the alloy composition to form a turbocharger with a high Nb-TiAl alloy composition, which can reduce the weight of the rotating parts of the turbocharger and reduce the rotational inertia, so that the turbocharger responds more quickly, improves the engine power performance and fuel economy, and at the same time, the alloy turbocharger has higher strength and specific stiffness, and has better structural stability when subjected to high-speed rotation and high temperature and pressure, and is not easy to deform and damage;

[0104] Second, the present disclosure adopts the SEBM forming process to accurately scan the molten high Nb-TiAl alloy powder layer by layer according to the three-dimensional model to produce complex-shaped structures, such as complex cooling channels, twisted blades, etc., which is beneficial to optimize the performance and efficiency of the supercharger. By controlling the oxygen content in the powder making process, SEBM forming parameters, and subsequent heat treatment and fluorination treatment, the microstructure and properties of the high Nb-TiAl alloy can be accurately controlled to meet the requirements of different working conditions and reduce the difficulty of processing. In addition, through the synergistic effect of heat treatment and fluorination treatment, the high-temperature oxidation resistance and creep performance of the turbocharger can be improved, deformation can be avoided, and the service life can be extended.

[0105] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present disclosure, but the present disclosure is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and substance of the present disclosure, and these modifications and improvements are also considered to be within the scope of protection of the present disclosure.

Claims

1. A method for manufacturing a high Nb-TiAl alloy turbocharger, characterized in that: The manufacturing method comprises: The high Nb-TiAl alloy powder is prepared by the rotating electrode powder making method through the integrated control technology of oxygen content in the whole process; The high Nb-TiAl alloy powder is scanned and melted layer by layer by using a SEBM forming process to form a high Nb-TiAl alloy turbocharger; The high Nb-TiAl alloy turbocharger is subjected to heat treatment and fluorination treatment.

2. The manufacturing method according to claim 1, characterized in that: The method of preparing high Nb-TiAl alloy powder by using a rotating electrode powder making method and an integrated control technology of oxygen content in the whole process includes: The titanium, aluminum and niobium metal powders are subjected to two consumable smelting processes and one induction smelting process to form electrode rods, wherein the oxygen content of the electrode rods is below 500 ppm; Under the condition that the oxygen content is less than 0.2ppm, the electrode rod is crushed by using a plasma rotating electrode powder making device, and the crushed powder is screened and packaged under an argon atmosphere to form a high Nb-TiAl alloy powder, wherein the oxygen content of the high Nb-TiAl alloy powder is less than 670ppm.

3. The manufacturing method according to claim 1, characterized in that: In the high Nb-TiAl alloy powder, the atomic ratio of titanium, aluminum and niobium is (40-50):(40-50):(4-10).

4. The manufacturing method according to claim 3, characterized in that: The high Nb-TiAl alloy powder is Ti-45Al-8Nb.

5. The manufacturing method according to claim 1, characterized in that: The SEBM forming process is used to scan and melt the high Nb-TiAl alloy powder layer by layer to form a high Nb-TiAl alloy turbocharger, comprising: Preheating the substrate; Spread powder on the substrate according to a preset powder layer thickness, and preheat the powder layer with a preheating current to micro-sinter the powder; Selectively melting high Nb-TiAl alloy powder to form a molten layer; Preheating the molten layer for a second time; The powder is spread on the substrate repeatedly and the molten powder is scanned layer by layer to form a high Nb-TiAl alloy turbocharger.

6. The manufacturing method according to claim 5, characterized in that: The substrate preheating temperature is 1100-1200° C., and the time is 10-30 minutes; and / or, The temperature of preheating the powder layer is 1100-1200°C; and / or, The temperature for secondary preheating the molten layer is 1100-1200°C.

7. The manufacturing method according to claim 5, characterized in that: The process parameters for selective melting of powder are as follows: melting current is 10-12.5 mA, electron beam scanning speed is 3.5-5 m / s, scanning spacing is 100 μm, powder layer height is 40-60 μm, and density is greater than 98%.

8. The manufacturing method according to claim 1, characterized in that: The high Nb-TiAl alloy turbocharger is subjected to heat treatment, comprising: The high Nb-TiAl alloy turbocharger is first heat treated at 1400-1500° C. for 20-40 min; A second heat treatment of the high Nb-TiAl alloy turbocharger at 1300-1400° C. for 50-60 min; The high Nb-TiAl alloy turbocharger is subjected to a third heat treatment at 900-1000° C. for 50-60 min.

9. The manufacturing method according to claim 1, characterized in that: The high Nb-TiAl alloy turbocharger is subjected to fluorination treatment, comprising: In a fluorine-containing electrolyte, a high Nb-TiAl alloy turbocharger is treated for 10-30 minutes using liquid phase electrolytic plasma deposition technology to implant fluorine ions into the surface of the high Nb-TiAl alloy and grow a F-containing oxide film in situ.

10. The manufacturing method according to claim 9, characterized in that: The fluorine-containing electrolyte comprises a first component and a second component; wherein, The first component is sodium fluoride or potassium fluoride; The second component is ethanol or ethylene glycol.

Citation Information

Patent Citations

  • Quick manufacturing method of titanium-aluminum alloy composite part

    CN102941343A

  • Method for oxidizing anode of titanium-aluminum alloy in fluoride-added ethylene glycol solution

    CN104532321A

  • Method for improving high-temperature oxidation resistance of high Nb-TiAl alloy

    CN114657501A

  • Electron beam selective melting TiAl alloy and preparation method

    CN118513565A

  • INTERMETALLIC ALLOY BASED ON THE γ-TiAl PHASE FOR THE MANUFACTURE OF A LOW-PRESSURE TURBINE BLADE OF A GAS TURBINE ENGINE AND A METHOD FOR MANUFACTURING A BLADE BLANK FROM AN INTERMETALLIC ALLOY BASED ON THE γ-TiAl PHASE

    RU2777775C1

Cited By

  • Layered regulation and control method for microstructure of additive manufacturing titanium-aluminum alloy

    CN120060689A